Proceedings of the National Seminar on Water Management and Control at Farm Level - National Seminar on Water Management and Control at Farm Level (1973 : Alur Setar); Lim, Cheong Chup; Khoo, Soo Hock; Thamutaram, S. (Kuala Lumpur : Ministry of Agriculture and Rural Development, 1973)
28